A Fully Automated Pipeline for Normative Atrophy in Patients with Neurodegenerative Disease - Rummel, Christian; Aschwanden, Fabian; McKinley, Richard; Wagner, Franca; Salmen, Anke; Chan, Andrew; Wiest, Roland (Frontiers in Neurology, 2018)
Introduction Volumetric image analysis to detect progressive brain tissue loss in patients with multiple sclerosis (MS) has recently been suggested as a promising marker for “no evidence of disease activity”. Software packages for longitudinal whole-brain volume analysis in individual patients are already in clinical use, however, most of these methods have omitted region-based analysis. Here, we suggest a fully automatic analysis pipeline based on the free software packages FSL and FreeSurfer. Material and Methods Fifty-five T1-weighted magnetic resonance imaging (MRI) datasets of five patients with confirmed relapsing–remitting MS and mild to moderate disability were longitudinally analyzed compared to a morphometric reference database of 323 healthy controls. After lesion filling, the volumes of brain segmentations and morphometric parameters of cortical parcellations were automatically screened for global and regional abnormalities. Error margins and artifact probabilities of regional morphometric parameters were estimated. Linear models were fitted to the series of follow-up MRIs and checked for consistency with cross-sectional aging in healthy controls. Results As compared to leave-one-out cross-validation in a subset of the control dataset, anomaly detection rates were highly elevated in MRIs of two patients. We detected progressive volume changes that were stronger than expected compared to normal aging in 4/5 patients. In individual patients we also identified stronger than expected regional decreases of subcortical grey matter, of cortical thickness and areas of reducing grey–white contrast over time. Conclusion Statistical comparison with a large normative database may provide complementary and rater independent quantitative information about regional morphological changes related to disease progression or drug-related disease modification in individual patients. Regional volume loss may also be detected in clinically stable patients.